The naked presenter : delivering powerful presentations with or without slides. - Reynolds, Garr, ....- (Berkeley : New Riders, 2011)
When we learn to present naked, we reach our audiences by communicating the essence of the message, stripping away all that is unnecessary and embracing the ideas of simplicity, clarity, honesty, integrity, and passion. If 'slideware' is used, the slides never steal the show or rise above serving a strong but simple supportive role. The ideas in the presentation may or may not be radical, earth shattering, or new, but there is freshness to the approach and content that makes a lasting impression. In this invaluable resource from the author for the best-selling books Presentation Zen and Presentation Zen Design, you will discover how to get to the core of your message and deliver presentations that are as natural as they are memorable. Whether you are just in the planning stages or need advice for a talk that begins in an hour, you'll find wisdom in The Naked Presenter that you can use to connect deeply with your audience and deliver a great presentation. Reynolds is a speaker, consultant, a writer, and designer. He is a long-time student of Zen arts - and is currently an Associate Professor of management at Kansai Gaidai University in Japan. In his first two books Presentation Zen and Presentation Zen Design, he wrote about tools for planning and designing successful presentations. In this book, he focuses on the delivery of the presentation...how presenters can deliver natural and memorable presentations that connect deeply with the audience.
Keywords: Mondelinge communicatie